In Vitro Evaluation of the Effects of Different Chemical Solvent Agents on Shear Bond Strength of Ceramic Orthodontic Brackets - Hande Uzunçıbuk; Süleyman Evren Öztaş (Galenos Yayinevi, 2023)
Objective:In this study, the effects of different chemical solvents such as acetone, ethanol, dimethyl sulfoxide (DMSO), peppermint oil, and hot water on the shear bond strength (SBS) of mechanically and chemically bonded ceramic brackets were examined. Their use for facilitation of the debonding process in practice was evaluated regarding the purposes of this study.Methods:One hundred and thirty-two human premolar teeth extracted for orthodontic purposes were randomly divided into 11 groups. SBS were applied using a universal test machine. The amount of residual adhesives was determined through adhesive remnant index scoring. Scanning electron microscopy (SEM) images were examined to determine the effects of solvents on the enamel surface.Results:In all test groups, the highest SBS values were found in the ethanol 5- and 15-minutes groups. SEM examination showed micro-cracks in all groups. Increased SBS values were also found in 5- and 15-minutes groups of hot water and DMSO, while both peppermint oil groups had similar SBS values as the control group. SBS values of both acetone 5- and 15-minutes groups were found to be lower than the control and other groups.Conclusion:Acetone application for 5 or 15 minutes before debonding of ceramic brackets could be an alternative clinical approach to prevent enamel damage and facilitate debonding.